The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jmedchem.0c02104
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Plasmodium falciparum HDAC1 Inhibitors with Dual-Stage Antimalarial Potency and Improved Safety Based on the Clinical Anticancer Drug Candidate Quisinostat

Abstract: Previously, we identified the clinical anticancer drug candidate quisinostat as a novel and potent antimalarial lead compound. To further enhance the antimalarial effect and improve safety, 31 novel spirocyclic hydroxamic acid derivatives were synthesized based on the structure of quisinostat, and their antimalarial activities and cytotoxicity were evaluated. Among them, compound 11 displayed broad potency in vitro against several multiresistant malarial parasites, especially two artemisinin-resistant clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Quisinostat demonstrates high antitumoral efficacy when dissolved in DMSO-water mixture with selectivity index of 9 [48]. In vitro anti-proliferative activity of quisinostat-PPEG complexes in the absence of co-solvent was demonstrated using two cell lines-A549 lung cancer cells and WM115 human melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Quisinostat demonstrates high antitumoral efficacy when dissolved in DMSO-water mixture with selectivity index of 9 [48]. In vitro anti-proliferative activity of quisinostat-PPEG complexes in the absence of co-solvent was demonstrated using two cell lines-A549 lung cancer cells and WM115 human melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ruoxi Li et al reported this year [ 45 ] their results of a new series of Pf HDAC1 inhibitors with dual-stage antimalarial potency and improved safety which was based on structural modifications of quisinostat. Quisinostat (16) showed potent antimalarial in vitro activity [ 46 ] and inhibited both wild-type and drug-resistant P. falciparum strains with IC 50 values 5–7 nM.…”
Section: Epigenetics: a New Antimalarial Biological Targetmentioning
confidence: 99%
“…The authors also point out that several compounds (31c, 31e, 31s, 31t) developed in the series showed interesting antiplasmodial activities, IC 50 (Pf 3D7) = 0.0052-0.12 µM, and good selectivity indexes, SI = 417-889, thus, representing a valuable starting point for the development of novel drug candidates (Table 3). [45] their results of a new series of Pf HDAC1 inhibitors with dual-stage antimalarial potency and improved safety which was based on structural modifications of quisinostat. Quisinostat (16) showed potent antimalarial in vitro activity [46] and inhibited both wild-type and drug-resistant P. falciparum strains with IC 50 values 5-7 nM.…”
Section: Histone Deacetylase (Hdac) Inhibitionmentioning
confidence: 99%
“…Since PfHDAC1 remains a very attractive drug target, further chemical optimization of JX21108 should be undertaken. Most recently, while main problem of the series remains the potential toxicity, the same research group reported the synthesis of a novel quisinostat derivative combining enhanced pharmacokinetics, multistage killing activity, and high potency against P. falciparum multiresistant strains [12] . Taken together, these data suggest that targeting the epigenome machinery may constitute a relevant alternative strategy to cure and prevent malaria, overcome antimalarial resistance, and control human‐to‐mosquito transmission, opening a new avenue for reaching the ambitious but indispensable goal of malaria eradication.…”
Section: Figurementioning
confidence: 99%
“…ChemMedChem the same research group reported the synthesis of a novel quisinostat derivative combining enhanced pharmacokinetics, multistage killing activity, and high potency against P. falciparum multiresistant strains. [12] Taken together, these data suggest that targeting the epigenome machinery may constitute a relevant alternative strategy to cure and prevent malaria, overcome antimalarial resistance, and control human-to-mosquito transmission, opening a new avenue for reaching the ambitious but indispensable goal of malaria eradication. Experiments showed that JX21108 could eliminate various stages of the parasites in vivo.…”
mentioning
confidence: 96%